Analysis of the Murabahah contract financing system on People's Business Credit (KUR) at PT. Bank Syariah Indonesia Kcp. Sukabumi Sudirman - Safitri, Mutiara Rintan; Kartini, Tina; Martaseli, Evi (Universitas Dehasen Bengkulu, 2023)
Murabahah financing is a transaction of selling goods by stating the acquisition price and profit (margin) agreed upon by the seller and buyer. Murabahah is a type of buying and selling that is permitted by sharia and is a business interaction or muamalat tijariyah. The legal basis for buying and selling Murabahah is found in the Qur'an, Al-Hadith and Fatwa of the National Sharia Council (DSN-MUI). Public knowledge about KUR financing has not been widely distributed, 7 out of 10 Prospective Customers do not know how the KUR application process is, Prospective Customers do not understand the KUR application procedure, Prospective Customers do not meet the requirements that have been set. This study aims to determine the Murabahah Financing System on People's Business Credit (KUR) and Analyze the feasibility of Murabahah Financing on People's Business Credit (KUR) at PT. Bank Syariah Indonesia Kcp. Sukabumi Sudirman. The method used in this study is qualitative research method with a descriptive approach. This study used primary and secondary data sources through observation, interviews and documentation. Based on the results of the study, it shows that the financing system for Murabahah contracts on People's Business Credit (KUR) uses a Murabahah bil wakalah contract. The system for applying for People's Business Credit (KUR) financing that is implemented at PT. Bank Syariah Indonesia Kcp. Sukabumi Sudirman is in accordance with the Standard Operating Procedures (SOP) set by the Financial Services Authority (OJK) which includes several stages, namely: the stage of submitting financing and verifying documents (Free Screening), the stage of financing analysis, the stage of visits (surveys), the stage of giving decisions (terms for financing approval), the stage of proof of documents and contracts, the stage of financing disbursement and the monitoring stage. In analyzing the feasibility of financing People's Business Credit (KUR) PT. Bank Syariah Indonesia has implemented the 5C Principles according to theory (M. L. I. Nasution, 2018), namely Character, Capital, Capacity, Conditions, Collateral (Guarantee).